Tópicos sobre a articulação microrregional no pós-desenvolvimento : Plano Diretor Alternativo e o caso de Vitória/Serra - Nunes, Orlando Vinicius Rangel (2015)
This research aims to relate three core subjects: 1) the crisis of the Master Plan, marked by the collapse of urban policies; 2) planning dilemmas in micro-regional scale; and 3) the exhaustion of the right to the city and the deprivation of spatial justi